Long-Distance Dating Relationships, Relationship Dissolution, and College Adjustment. (August 2017) - Waterman, Emily A.; Wesche, Rose; Leavitt, Chelom E.; Jones, Damon E.; Lefkowitz, Eva S.
Long-distance dating relationships (LDDRs) and the dissolution of these relationships may have implications for day-to-day affect and behaviors. The current study examined the associations of relationship status, long-distance relationship dissolution, and daily location with daily positive affect, loneliness, university activity engagement, and alcohol use. College students ( n = 718, 51.5% female, 43.9% White/European American, 29.7% Asian/Asian American/Hawaiian/Pacific Islander, 25.5% Hispanic/Latino American, and 21.7% Black/African American; M = 18.4 [0.4] years old) completed up to 14 consecutive daily diary surveys twice during their first year. Students in LDDRs had less positive affect and were lonelier when they were on campus than off campus and tended to engage in university activities on fewer days than other students. Daily affect and behavior did not differ depending on whether students dissolved or maintained their LDDR.